Space-time modeling of agricultural landscape variability using AgSimGIS - Ascough, James C., II, author; Green, Timothy R., author; Cipra, Jan E., author; Ahuja, Lajpat R., author; Ma, Liwang, author; Colorado State University, publisher (Colorado State University. Libraries, 2004)
Most agricultural water quality models are based on umped parameterizations of spatial process. The AgSimGIS water quality tool has been developed to predict space-time planning scenarios across spatially variable agricultural landscapes. The tool runs under the ArcGIS 8.3 environment, and consists of a multi-functional system for simulation modeling and spatial data storage, analysis, and display. AgSimGIS offers a spatial framework for integrating a complex, agricultural system water quality a model (modified USDA-ARS RZWWQM) with interaction between simulated land areas via overland runoff and runon. AgSimGIS also provides the increased interface sophistication necessary for distributed hydrologic modeling. AgSimGIS development history, including an overview of the major GIS and simulation modeling components, will be presented.
Hydrology days 2004
AGU hydrology days 2004
24th annual AGU hydrology days was held at Colorado State University on March 10-12, 2004.